A simple pincer-type chemosensor for reversible fluorescence turn-on detection of zinc ion at physiological pH range. (30th March 2015) - Lin, Qi; Cai, Yi; Li, Qiao; Chang, Jing; Yao, Hong; Zhang, You-Ming; Wei, Tai-Bao
Abstract : A dihydrazone based pincer-type chemosensor (Y ) which could detect zinc at physiological pH range with reversible fluorescence "Off–On–Off". Abstract : A new, highly selective and sensitive pincer-type chemosensor (Y ) for zinc ion with turn-on fluorescence behavior in physiological pH range solution was developed.Y is based on bi-hydrazone derivatives, which contain pyridine as the fluorescent group and a hydrazone bond as recognition site. The selectivity mechanism ofY for zinc is based on the combined effects of the inhibition of excited-state intramolecular proton transfer (ESIPT) and –HCN– isomerization, as well as chelation-enhanced fluorescence. The entire process takes less than 15 seconds. The minimum detection limit ofY for zinc reaches 1.39 × 10 −8 M. Moreover, Y can conveniently detect zinc in test strip form, and it can be recycled.